Family Relationships, Dialogue, and Philosophy for Children: - Giuseppina D'Addelfio; Maria Vinciguerra (Ignatianum University Press, 2021)
The paper deals with the importance of words and dialogue in family education. In the first part, some evidence of an action research is presented - shaped in a hermeneutic phenomenological framework and thanks to the Philosophy for Children method and materials. Then some key words are pointed out, meant as formative goals for parents' educational support, so as to highlight the importance of dialogue among generations and, mainly, of the ethical responsibility of parents in education.